ANALISIS KUALITAS WEBSITE PO. AGRAMAS MENGGUNAKAN METODE PIECES - Indah Klara Butar Butar; Anie Yoraeni - Universitas Nusa Mandiri (APMMI - Asosiasi Profesi Multimedia Indonesia, 2022)
Abstract - Website is a page for sharing information that is provided via the internet which can be accessed in various parts of the world. PO website. Agramas is a website as a media for promotion, sales and broadcast news in the form of text, animation and images. The purpose of this study was to analyze the quality of the PO.Agramas website to determine the level of website quality based on user perceptions. To analyze the quality of this website, it is done using the PIECES method, namely performance (performance), information (information), economy (economics), control (control), efficiency (efficiency), service (services) and customer satisfaction variables. Meanwhile, for testing in the analysis of this website using the SPSS version 23 application by conducting validity tests, reliability tests and linear regression analysis. From the results of the validity and reliability test shows that the overall results of the statement items are valid and reliable based on the results of the questionnaire that has been given. By analyzing the PO.Agramas website, it can be seen that from the six dimensions of the analysis of the PIECES method, it is stated that the PO.Agramas website is in accordance with user needs and can provide good service by providing good website quality. Keywords: PIECES, Analysis, Website Quality, User Satisfaction Abstrak - Website merupakan salah satu halaman untuk berbagi informasi yang di sediakan melalui jalur internet yang dapat diakses di berbagai belahan dunia. Website PO. Agramas merupakan website sebagai media promosi, penjualan serta menayangkan berita-berita dalam bentuk teks, animasi maupun gambar. Tujuan dari penelitian ini adalah menganalisis kualitas website PO.Agramas untuk mengetahui tingkat kualitas website berdasarkan persepsi pengguna. Untuk menganalisis kualitas website ini dilakukan dengan menggunakan metode PIECES yaitu performance (kinerja), information (informasi), economy (ekonomi), control (pengendalian), efficiency (efisiensi), service (layananan) dan variabel kepuasan pelanggan. Sedangkan untuk pengujian dalam analisis website ini menggunakan aplikasi SPSS versi 23 dengan melakukan uji validitas, uji reabilitas dan analisis regresi linear. Dari hasil uji validitas dan reabilitas menunjukkan bahwa keseluruhan hasil item-item pernyataan valid dan reliable berdasarkan hasil kuisoner yang telah diberikan. Dengan melakukan analisis pada website PO.Agramas dapat diketahui bahwa dari enam dimensi analisis dari metode PIECES tersebut menyatakan bahwa website PO.Agramas sesuai dengan kebutuhan pengguna serta dapat memberikan pelayanan yang baik dengan memberikan kualitas website yang baik. Kata Kunci : PIECES, Analisis, Kualitas Website, Kepuasan Pengguna